Konsep dan realiti dalam pekembangan habitat manusia dan perubahan iklim - Jamaluddin Md. Jahi, (Universiti Kebangsaan Malaysia, 2010)
Is it true that human habitat development has caused climate change? Or, is it true that climate change has already occurred and human habitat development is merely an added catalyst to an already occurring phenomenon. Studies carried out up to the present clearly indicate that climate change has occurred since thousand million of years ago and is still occurring to the present. During such a long period of time whatever happened in the past could not have possibly been due to development and growth of human habitats because human existence is said to be less than 2.5 million years ago. Nevertheless, since about five million years ago the earth was still experiencing climate change based on a number of evidences, especially related to the rise and fall of sea level due to the built-up and melting of continental ice sheets. However, since a few centuries ago with the growth and development of human habitats due to rapid population growth and their activities, the already existing climate change has been further enhanced. This article discusses on the concept and reality of human habitat development and climate change